Desain Pembelajaran IPS Berbasis Project Based Learning Pada Tingkat SD/MI - Nur Fariha Maulidia; Dewi Ayu Istiqomah (FKIP, Universitas Palangka Raya, 2023)
Project based learning requires teachers to manage learning on a project basis for students. Project-based learning activates students in learning activities. Project-based learning requires solving problems by applying the skills of researching, analyzing, creating, and presenting learning products based on real experiences. Social studies subjects at the elementary school level usually present several problems that can be applied with project-based learning in solving them. And Project Based Learning or project-based learning is a learning process that focuses on students and everything that students do to receive knowledge. In learning with a project based learning metode, students are expected to be able to solve real problems to be solved. The problem itself can stimulate the activeness of students to think or in other words allow students to find and solve problems and communicate ideas in new and appropriate ways. As educators, we always try to make learning calm, comfortable, and fun, that's how we make students a source of project activities to produce something that is the goal of the learning